Enhancing Fast-Charge Capabilities in Solid-State Lithium Batteries through the Integration of High Li0.5La0.5TiO3 (LLTO) Content in the Lithium-Metal Anode - Cao, Chencheng; Zhong, Yijun; Zhao, Leqi; Seneque, Hannah; Shao, Zongping (2023)
Solid-state batteries (SSBs), which have high energy density and are safe, are recognized as an important field of study. However, the poor interfacial contact with high resistance, the dendrite problem, and the volume change of the metallic lithium anode prevent the use of SSBs. Li0.5La0.5TiO3 (LLTO) particles and molten lithium were used to create a high-performance LLTO-Li composite lithium with a sequential ion-conducting phase. With garnet electrolytes, this lithium has better wettability and reduced surface tension. To compensate for the lithium depletion that occurs during stripping, the Li-Ti phase with a high ionic diffusion coefficient that forms in the anode can rapidly transport lithium from the bulk to the solid-state interface, ensuring tight interface contact, preventing the formation of gaps, and homogenizing the current and Li+ flux. The LLTO-Li| LLZTO| LLTO-Li symmetric cell exhibits a good cyclic stability of 1000 h at room temperature, a low interfacial resistance of 22 Ω cm2, and a high critical current density of 1.2 mA cm-2. Furthermore, fully built cells with a LiFePO4 cathode showed outstanding cycling performance, maintaining 95% of their capacity after 900 cycles at 1 C and 92% capacity retention after 100 cycles at 2 C.